1988
DOI: 10.1152/ajpheart.1988.255.4.h847
|View full text |Cite
|
Sign up to set email alerts
|

Independent blockade of cerebral vasodilation from acetylcholine and nitric oxide

Abstract: We investigated the mechanisms of cerebral arteriolar dilation from topical acetylcholine and the nitrovasodilators, sodium nitroprusside, nitroglycerin, and nitric oxide, in anesthetized cats equipped with cranial windows for the observation of the cerebral microcirculation. Acetylcholine-mediated dilation was eliminated by topical methylene blue. This blockade was reversed by either topical superoxide dismutase, catalase, or deferoxamine. Nitroprusside- and nitric oxide-induced dilation were not affected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 0 publications
8
58
0
Order By: Relevance
“…23 If this is correct, the effect of H 2 O 2 on EDRF production may be explained because the oxidation of these essential SH groups may render the endothelium unable to produce EDRF. Our findings in the present study and earlier findings 19 are consistent with the possibility that the EDRF from acetylcholine in the cerebral vessels might be a nitrosothiol, which is capable of activating guanylate cyclase directly without the necessity for an interaction with tissue components. Our findings with cysNO support this view.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…23 If this is correct, the effect of H 2 O 2 on EDRF production may be explained because the oxidation of these essential SH groups may render the endothelium unable to produce EDRF. Our findings in the present study and earlier findings 19 are consistent with the possibility that the EDRF from acetylcholine in the cerebral vessels might be a nitrosothiol, which is capable of activating guanylate cyclase directly without the necessity for an interaction with tissue components. Our findings with cysNO support this view.…”
Section: Resultssupporting
confidence: 93%
“…This view is supported by the demonstration of partial restoration of the response to nitroprusside after replenishment of SH groups with A^-acetyl-L-cysteine. The present findings are consistent with earlier results 19 in which we used nitro blue tetrazolium, a dye that oxidizes SH groups, to block the vasodilating effect of nitroghycerin, nitroprusside, and nitric oxide. Nitro blue tetrazolium in these experiments did not influence the response to acetylcholine.…”
Section: Resultssupporting
confidence: 93%
“…Production of superoxide anion inactivates NO (Marshall et al, 1988;Rubanyi & Vanhoutte, 1986;Kobayashi & Kamata, 2001) and dismutation of free radicals has generally (Pieper et al, 1996;Hattori et al, 1991;Kamata & Kobayashi, 1996) but not always (Heygate et al, 1995) been found to improve impaired endothelium-dependent relaxation in experimental models of diabetes. Indeed, we recently reported that NO is metabolized by O 2 7 to NO 3…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a considerable body of evidence now suggests that in type I diabetes, the observed impairment of endothelial function may involve inactivation of NO by oxygen-derived free radicals (Meraji et al, 1987;Hattori et al, 1991;Pieper et al, 1992;Tesfamariam, 1994;Keaney and Vita, 1995;Kamata et al, 1996a;Ooboshi et al, 1997;Kobayashi and Kamata, 1999a, 2002b. In experimental models of type I diabetes, an enhancement of NO production (which in such models is diminished by superoxide anion) and dismutation of free radicals has generally been found to improve impaired endothelium-dependent relaxation (Rubanyi and Vanhoutte, 1986;Marshall et al, 1988;Kobayashi and Kamata, 2001). Convincing evidence indicates that the major enzymatic sources of vascular superoxide are NAD(P)H oxidase, xanthine oxidase, and uncoupled NOS (Landmesser and Harrison, 2001).…”
Section: Mechanisms Underlying Impaired Endothelial Function In Diabementioning
confidence: 99%